Pengaruh Lingkungan Teman Sebaya, Viral Marketing, Dan Customer Online Review Terhadap Keputusan Pembelian Impulsif Secara Online Di Shopee (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Angkatan 2018 Universitas Islam Malang) - Rika Amelia Wati; Muhammad Ridwan Basalamah; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine and analyze the influence of Peer Environment, Viral Marketing and Online Customer Reviews on Impulse buying behavior online at Shopee. The population in this study is the 2018 batch of students, Faculty of Economics and Business, Islamic University of Malang who have purchased products at Shopee. The data collection method in this study used a questionnaire with a total sample of 100 respondents. The independent variables in this study are Peer Environment, Viral Marketing and Online Customer Reviews and the dependent variable is the Impulsive Purchase Decision. The analytical method used in this study is multiple linear regression analysis and processed using SPSS 25. The results of this study simultaneously show that Peer Environment, Viral Marketing and Online Customer Reviews have a positive and significant effect on Impulse buying behavior. Partially, Peer Environment and Online Customer Reviews have a significant effect on Impulsive Purchase Decisions, while Viral Marketing has no effect on Impulse buying behavior. Keywords: Peer Environment, Viral Marketing, Online Customer Reviews, Impulsive Buying Behavior.